PENDIDIKAN SEPANJANG HAYAT PERSPEKTIF AL-QUR’AN DAN HADIS TARBAWI - Mutiara; Rahendra Maya Rahendra Maya; Abdul Jabar Idharudin Abdul Jabar Idharudin (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
Abstract Lifelong education has not yet been systematically formulated within the Islamic perspective based on the Qur’an and Hadith, and is therefore still narrowly understood as formal education. This study aims to analyze the conceptual construction of lifelong education from the perspective of Qur’anic exegesis (tafsir) and educational (tarbawi) hadith, as well as to explain its relevance for the development of contemporary Islamic education. The research employs a qualitative approach with a library research design. Data were collected through documentation of Qur’anic verses, tarbawi hadith, classical tafsir works, and Islamic education literature, and were analyzed using content analysis techniques through stages of data reduction, categorization, interpretation, and conceptual synthesis. The findings indicate that lifelong education in Islam constitutes an integral theological principle encompassing intellectual, spiritual, moral, and social dimensions. This concept positions learning as a continuous obligation, a means of self-purification, and an instrument of civilizational transformation. Consequently, Islamic education needs to reorient its learning paradigm toward strengthening a culture of lifelong learning through integrative curricula, reflective methods, and the development of literacy ecosystems within families, schools, and society.